A Molecule‐Based Single‐Photon Source Applied in Quantum Radiometry. Issue 2 (22nd October 2019) - Lombardi, Pietro; Trapuzzano, Marco; Colautti, Maja; Margheri, Giancarlo; Degiovanni, Ivo Pietro; López, Marco; Kück, Stefan; Toninelli, Costanza
Abstract: Single‐photon sources (SPSs) based on quantum emitters hold promise in quantum radiometry as metrology standard for photon fluxes at the low light level. Ideally this requires control over the photon flux in a wide dynamic range, sub‐Poissonian photon statistics, and narrow‐band emission spectrum. In this work, a monochromatic SPS based on an organic dye molecule is presented, whose photon flux is traceably measured to be adjustable between 144 000 and 1320 000 photons per second at a wavelength of (785.6 ± 0.1) nm, corresponding to an optical radiant flux between 36.5 and 334 fW. The high purity of the single‐photon stream is verified, with a second‐order autocorrelation function at zero time delay below 0.1 throughout the whole range. Such molecule‐based SPS is hence used for the calibration of a single‐photon avalanche detector against a low‐noise analog photodiode traceable to the primary standard for optical radiant flux (i.e., the cryogenic radiometer). Due to the narrow bandwidth of the source, corrections to the detector efficiency arising from the spectral power distribution are negligible. With this major advantage, the developed device may finally realize a low‐photon‐flux standard source for quantum radiometry. Abstract : Here a molecule‐based single‐photon source (SPS) ready for application in quantum metrology is presented. The source is linked to a national radiometric standard for optical fluxes, assessing the device in terms of an absolute SPS. Finally it is deployed for the direct calibration of a single‐photon avalanche detector, on a large range of optical radiant fluxes.